Unveiling Risk Factors in a Patient with Silicotuberculosis: A Case Report - Sadikim, Rahel Yuana; Hasan, Helmia; Hidayat , Agus; Duta, Garinda Alma; Wati, Farah Fatma (Jurnal Respirasi, 2025)
Introduction: Silicosis, an occupational lung disease caused by crystalline silica dust, is often complicated by tuberculosis (TB). The epidemiological triad suggests disease results from imbalanced interactions between the host, agent, and environment. Case: A 63-year-old underweight man presented with decreased consciousness after consuming drugs, chronic cough, low-grade fever, weight loss, and lower urinary tract symptoms. He was a smoker, drug abuser, and alcoholic. He had worked as a construction worker for 33 years without personal protective equipment (PPE). The patient lived in substandard housing, and three neighbors had a history of TB. Urine toxicology was positive for amphetamine. Abdominal ultrasound showed prostate enlargement. A chest X-ray showed fibroinfiltrates, cavities, and reticulogranular patterns. A high-kV chest X-ray revealed profusion levels of 1/2 S/S and 1/1 P/P. Contrast chest computed tomography (CT) showed tree-in-bud patterns, reticulogranular patterns, small nodules, and fibrosis. Brain CT was normal. GeneXpert sputum confirmed Mycobacterium tuberculosis (MTB), and bronchoalveolar lavage (BAL) spectrophotometric detected 38.90 ppm silica. He was diagnosed with amphetamine intoxication, benign prostatic hyperplasia, and silicotuberculosis. Haloperidol, tamsulosin, and anti-TB therapy were administered, while silicosis had no specific treatment. He was advised to change job to reduce silica exposure and planned to receive housing renovation assistance from the Health Office of Surabaya. The patient was declared cured after completing six months of TB treatment. Conclusion: The host factors included nutritional status, comorbidity, and personal habits; the agent factor was MTB; and the environmental factors included inadequate ventilation, high housing density, close contact with TB patients, and occupational conditions. A holistic identification of host, agent, and environmental risk factors is essential for understanding the development, prevention, and diagnosis of silicotuberculosis.